Startups: types, stages of development and characteristics of successful companies - Momirović, Andjela (Ekonomija - teorija i praksa, 2025)
Understanding this new business approach is crucial, and it is necessary to define startups, their types, and stages of development. This research aims to define startups, explain how they operate, describe the phases they undergo, the factors influencing their decisions, and the stages of development from their inception to their final phase. The analysis will draw conclusions regarding the parameters that guide startup operations. First, the concept of startups will be explained, including the decisions made during their creation and the choice of startup type at the outset. Finally, after presenting the characteristics that these companies must possess to achieve their goals and ensure the greatest possible success and development within a short timeframe (usually 5 years), conclusions will be drawn.